131 Synergistic Value of Simultaneous Stress Echocardiography and Carotid Ultrasound Performed in Patients with Suspected Angina without Known Coronary Artery Disease for The Prediction of Outcome. (3rd June 2016) - Ahmadvazir, Shahram; Zacharias, Kostas; Shah, Benoy; Kinsey, Christopher; Young, Grace; Senior, Roxy
Abstract : Background: Presence of carotid artery disease has been shown to predict cardiovascular risk beyond traditional risk factors. However, the potential impact of carotid disease (CD) in patients undergoing stress echocardiography (SE) for new-onset chest pain without known coronary artery disease (CAD) is unknown. We hypothesised that information of ischemia and atherosclerosis which can be achieved simultaneously by ultrasound (SE and carotid ultrasound) can provide incremental prognostic information in these patients. Methods: Consecutive patients with no previous history of CAD investigated with SE for suspected angina underwent a simultaneous carotid ultrasound. Carotid plaque burden was assessed. Patients were followed up for combined major adverse cardiac events (MACE) of all-cause mortality, non-fatal myocardial infarction and unplanned coronary revascularization. Results: Of the 591 patients, (269 male (46%), mean age 59 ± 11 years), 67 (11%) demonstrated myocardial ischemia by SE. Prevalence of carotid plaque disease was higher (59%) but similar in normal and abnormal SE patients (58% vs. 66%, p = 0.22). At a mean of 37 months, 580 (98%) could be followed up during which 40 MACE occurred. In the multivariable model pre-test probability of CAD (p = 0.001), abnormal SE (p < 0.0001) and plaque burden (p < 0.0001) predicted MACE after adjusting for age, gender, cardiac risk factors and baseline drug therapy. MACE rate/year increased from 0.9% vs. 1.95% vs. 4.23% vs. 9.58% (p < 0.0001) in patients with no plaque and normal SE vs. presence of plaque and normal SE vs. no plaque and abnormal SE vs. plaque and abnormal SE, respectively. Figure demonstrates the prognostic value of simultaneous carotid plaque assessment and SE. When prognosis was assessed in a hierarchical manner as done clinically (pre-test probability of CAD followed by SE and carotid ultrasound), it showed significant increment in global chi square from 22.1 to 48.9 to 78.5 (p < 0.0001). Conclusion: In patients with suspected stable angina but without known CAD simultaneous SE (for ischemia) and carotid ultrasound (for atherosclerosis) provided synergistic prognostic value. This study supports simultaneous carotid ultrasound in such patients investigated by SE and has implications in primary prevention treatment.